Acceptability and potential impacts of innovative E-Portfolios implemented in E-Learning systems for clinical training. Issue 6 (December 2018) - Elshami, Wiam E.; Abuzaid, Mohamed M.; Guraya, Shaista S.; David, Leena R.
الملخص : أهداف البحث: هناك أدلة متزايدة على أن استخدام المحافظ الإلكترونية له تأثير إيجابي على خبرة التعلم. لكن، لم تظهر الأدبيات بيانات كافية عن فعالية المحافظ الإلكترونية في التعليم الطبي. أجريت هذه الدراسة لتقييم القبول والتأثيرات المحتملة للمحفظة الإلكترونية لطلاب الأشعة التصويرية. طرق البحث: أجريت هذه الدراسة الكمية المقطعية خلال العام الأكاديمي ٢٠١٦-٢٠١٧ على الطلاب أثناء التدريب السريري. تم توزيع استبانة ذاتية على مجموعة مختارة من الطلاب. أكمل جميع المشاركين نموذج الموافقة قبل تنفيذ الاستبانة. النتائج: من بين ٧٥ طالبا، أكمل ٦٦ الاستبانة (معدل الاستجابة؛ ٨٨٪). تم تحديد خبرات الطلاب، دعم التعلم للطلاب والتحديات للمحفظة الإلكترونية. اعتبر واحد واربعون طالبا (٦٢٪) أن المحفظة الإلكترونية تسهل التنظيم الفعال لعملهم، ووافق ٤٠ (٦١٪) على أن المحفظة الإلكترونية عزّزت مهاراتهم المهنية. في المقابل، أدرك الطلاب وجود علاقة سلبية بين دعم التعلم لدى الطلاب والاستفادة المستقبلية للمحفظة الإلكترونية. ووجد أن الاستخدام المستقبلي للمحفظة الإلكترونية يرتبط ارتباطا إيجابيا بالتحديات والالتزام بالمواعيد النهائية، معاملات الترابط ٠.٣٧١ و٠.١٥٢على التوالي. الاستنتاجات: استخلصت الدراسة أن الدعم الفني المستمر للمحفظة الإلكترونية طوال الدورة له دور محتمل في تعزيز خبرة التعلم. التدريب المناسب لدمج المحافظ الإلكترونية في التعليم والتعلم يمكن أن يؤدي إلى إثراء البيئة التعليمية. وردود فعل الطلاب وأعضاء هيئة التدريس هي حجر الزاوية الرئيس لنجاح المحفظة الإلكترونية. Abstract: Objective: There is growing evidence that use of E-portfolios has a positive effect on learning experience. However, literature has not shown sufficient data about the effectiveness of E-portfolios in medical education. This study was conducted to assess the acceptability and potential impacts of E-portfolio use for undergraduate radiography students. Methods: This cross-sectional quantitative study was conducted during the academic year 2016–2017 on students studying clinical courses. A self-administered questionnaire was distributed to the selected cohort of students. All participants completed the consent form before answering the questionnaire. Results: Of 75 students, 66 completed the survey (response rate; 88%). Students' experience, students' learning support, and the challenges of E-portfolio use were identified. Forty-one (62%) students perceived that E-portfolios facilitated the effective organization of their work, and 40 (61%) agreed that E-portfolios enhanced their professional skills. In contrast, the students perceived a negative correlation between students' learning support and future utilization of E-portfolios (correlation coefficient −0.394, p  = 0.05). Future utilization of E-portfolios was found to be positively correlated with challenges and commitment to deadlines, with correlation coefficients of 0.371 and 0.152, respectively. Conclusion: The study found that continuous technical support for E-portfolios throughout the course had a potential role in enhancing learning experience. Appropriate training for integrating E-portfolios into teaching and learning can potentially enrich the educational environment. Student and faculty feedback is the main cornerstone for E-portfolio success.